2003
DOI: 10.1016/s1074-5521(03)00160-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Specificity, Reactivity, and Antitumor Activity of DNA-Alkylating Pyrrole-Imidazole Diamides

Abstract: Three conjugates of imidazole (Im)-pyrrole (Py) diamide and a DNA-alkylating moiety derived from the antibiotic duocarmycin A were synthesized, and their sequence specificity, reactivity, and antitumor activity comparatively examined. Sequencing gel analysis indicated that ImPyDu (1) alkylates DNA at the 3' end of AT-rich sequences at micromolar concentration. ImPyDu86 (2) reacts with DNA at AT-rich sites together with dialkylation sites at micromolar concentration. ImPyLDu86 (3) efficiently alkylates dialkyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…30) containing a trans-alkene linker and n-propyl end group bind DNA in AT rich regions with slightly different sequence selectivity to CC-1065 and with additional alkylation of guanine [74]. Similar compounds such as 53 have been prepared [75][76][77]. Hybrid 53 was shown to alkylate double stranded DNA predominantly at the purines of sequence 5'-PyG(A/T)CPu-3' of both strands (sites 1-3) by co-operative homodimer formation, indicating a potential application for duocarmycin hybrids in the development of novel sequence specific DNA-crosslinking agents [75].…”
Section: Bifunctional Alkylating Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…30) containing a trans-alkene linker and n-propyl end group bind DNA in AT rich regions with slightly different sequence selectivity to CC-1065 and with additional alkylation of guanine [74]. Similar compounds such as 53 have been prepared [75][76][77]. Hybrid 53 was shown to alkylate double stranded DNA predominantly at the purines of sequence 5'-PyG(A/T)CPu-3' of both strands (sites 1-3) by co-operative homodimer formation, indicating a potential application for duocarmycin hybrids in the development of novel sequence specific DNA-crosslinking agents [75].…”
Section: Bifunctional Alkylating Agentsmentioning
confidence: 99%
“…Hybrid 53 was shown to alkylate double stranded DNA predominantly at the purines of sequence 5'-PyG(A/T)CPu-3' of both strands (sites 1-3) by co-operative homodimer formation, indicating a potential application for duocarmycin hybrids in the development of novel sequence specific DNA-crosslinking agents [75]. Comparison with similar agents where the polyamide is directly bonded to the CPI unit showed that the vinyl linker in 53 increased DNA alkylation efficiency and biological activity (average IC 50 = 5.62 nM in the Cancer Chemotherapy Centre of Japan's 39 human cancer cell line panel) [77].…”
Section: Bifunctional Alkylating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…46) We synthesized a series of alkylating diamides, ImPyDu, ImPyDu86, and ImPyLDu86, and evaluated their cytotoxicity using a panel of 39 human cancer cell lines. 47) The log IC 50 values of ImPyDu, ImPyDu86, and ImPyLDu86 were Ϫ4.59, Ϫ5.95, and Ϫ8.25, respectively. Array-based chip 472 Vol.…”
Section: )mentioning
confidence: 96%
“…We examined in detail comparative studies of DNA sequence-specific alkylation and the antitumor activity of the alkylating ImPy conjugates using high-resolution denaturing gel electrophoresis and the panel of 39 human cancer cell lines. 29 Recently, we found that alkylating Py-Im polyamides 9 and 10, which differ only in that the C-H atoms is substituted by an N atom in the second ring, showed significantly different cytotoxicity in the 39 human cancer cell line panel (Fig. 12).…”
Section: Recognition Of Dna Sequencesmentioning
confidence: 97%